Frekuensi Gangguan dan Energi Tak Tersalurkan Sebagai Indikator keandalan Sistem Jaringan Tegangan Menengah - Rusliadi Rusliadi; Yulianto La Elo (Universitas Darul Ulum, 2024)
The increasing need for electrical energy must be balanced with improved customer service. Customers will feel comfortable if they can enjoy an uninterrupted electricity supply in the form of a disconnection of the electricity supply for a certain period of time or what is commonly called the ENS (Energy Not Supplied) index and the AENS (Average Energy Not Supplied) index. The reliability of the electric power system is one of the things that is very important in order to maintain the performance of the three main pillars of PT. PLN (Persero). A reliable distribution network can be seen from the number of disruptions that often occur in the distribution network. Disruptions that arise in the distribution network arise due to internal factors such as less reliable distribution network components. In addition, it can also be caused by external factors such as natural disasters or the influence of trees and animals. Based on the results of the research that has been conducted, it is known that the occurrence of disruptions and the length of the duration of the disruption cause the Energy Not Supplied (ENS) value to increase as in April and July, the high duration of the blackout also makes the ENS higher, namely 792.857804 kW and 789.046811 kW. However, the distribution network at the Wagom feeder is still considered reliable in distributing electrical energy based on the SAIDI and SAIFI indices. From the research results, the SAIDI index at the Wagom feeder reached 8.96 hours/customer/year. While the SAIFI index at the Wagom feeder reached 2.08 times/customer/year.